A novel method for estimating the heading angle for underground Load-Haul-Dump based on Ultra Wideband. (March 2018) - Wu, Di; Meng, Yu; Gu, Qing; Ma, Fei; Zhan, Kai
This paper presents a system that measures the heading angle of underground Load-Haul-Dump (LHD) based on Ultra Wideband (UWB). The system is composed by two UWB modules. The heading angle gives the predictable information for the vehicle localization. Because of the features of underground mines, many current methods for estimating heading angle have limitations in this situation, such as the absence of Global Positioning System (GPS) and the high cost of the positioning methods based on beacons. The range resolution is proportional to the bandwidth of signal. So, the large system bandwidth of UWB offers high accuracy. We estimate the heading angle by measuring the angle between two UWB modules, which is implemented on LHD. The position error of the two modules directly decides the error of heading angle. This paper analyzes and discusses two-dimensional error in theory. The experimental results demonstrate that it is feasible to use the proposed method for an underground environment.